Local Government Policies in the Management of Coastal and Marine Resources Through Community Participation - Erga Yuhandra; Sarip Hidayat; Iman Jalaludin Rifa’i (UNIFIKASI : Jurnal Ilmu Hukum, 2023)
Natural resources have a significant role in supporting national development as a good natural resources management will generate foreign exchange for the country. This study aims to analyze the local governments’ and communities’ efforts in utilizing and managing coastal and marine resources as well as to find out the inhibiting factors in the utilization of coastal and marine resources to achieve environmental sustainability. The method used in this study was normative juridical research method, in which the study was carried out by examining and interpreting theoretical matters on principles, conceptions, doctrines, and legal norms relating to the management of coastal and marine resources. Meanwhile, the data analysis used was a juridical-qualitative analysis, where the analysis describes descriptive-analytical and prescriptive. The qualitative analysis, that is descriptive and prescriptive in nature, was carried out by ensuring that laws do not conflict with one another, paying attention to hierarchy and legal certainty, and examining both written and unwritten laws. Then, the type of data used in this study was primary legal materials in the form of laws and regulations. The results of the analysis showed that the management of coastal and marine resources must be carried out collaboratively between all parties to create an environmental sustainability-based management, and a synchronization and harmonization of legal products made by the central and local governments is needed to realize an optimal management of coastal and marine resources.